Project Wingman – A short survey of staff perception and lounge benefit in a large UK NHS Trust. Issue 4 (May 2022) - Brennan, Peter A.; Davidson, Mike; Fielding, Dave; Quek, Janine; Cornelius, Nicole; Knighton, John; Oeppen, Rachel S.
Abstract: Project Wingman is a novel initiative conceived early in the COVID-19 pandemic by two airline captains and a psychologist, which brings airline style lounges, staffed by volunteer air crew to NHS Trusts. The aim was to boost morale by providing airline style customer service for staff while on breaks. Over 50 lounges were opened across the NHS, staffed by up to 5000 volunteers. In this pilot study of one large Trust, we surveyed staff who visited the Wingman lounge. 100 completed questionnaires were used as an end point. All staff felt that the lounge was beneficial during COVID. 62% reported that they would visit the lounge even it was not attended by aircrew. 57% felt their wellbeing had suffered during the pandemic. A national study would be useful to assess the impact of the Wingman Lounges, but our pilot study highlights the importance of staff wellbeing and the value of taking breaks while at work. Many of the lessons learned in supporting colleagues during the pandemic could be used and adapted to help future wellbeing initiatives and aid retention of staff across the NHS.